Maize root lectins mediate the interaction with Herbaspirillum seropedicae via N-acetyl glucosamine residues of lipopolysaccharides. - Eduardo Balsanelli; Thalita Regina Tuleski; Valter Antonio de Baura; Marshall Geoffrey Yates; Leda Satie Chubatsu; Fabio de Oliveira Pedrosa; Emanuel Maltempi de Souza; Rose Adele Monteiro (PLoS ONE)
Herbaspirillum seropedicae is a plant growth-promoting diazotrophic betaproteobacterium which associates with important crops, such as maize, wheat, rice and sugar-cane. We have previously reported that intact lipopolysaccharide (LPS) is required for H. seropedicae attachment and endophytic colonization of maize roots. In this study, we present evidence that the LPS biosynthesis gene waaL (codes for the O-antigen ligase) is induced during rhizosphere colonization by H. seropedicae. Furthermore a waaL mutant strain lacking the O-antigen portion of the LPS is severely impaired in colonization. Since N-acetyl glucosamine inhibits H. seropedicae attachment to maize roots, lectin-like proteins from maize roots (MRLs) were isolated and mass spectrometry (MS) analysis showed that MRL-1 and MRL-2 correspond to maize proteins with a jacalin-like lectin domain, while MRL-3 contains a B-chain lectin domain. These proteins showed agglutination activity against wild type H. seropedicae, but failed to agglutinate the waaL mutant strain. The agglutination reaction was severely diminished in the presence of N-acetyl glucosamine. Moreover addition of the MRL proteins as competitors in H. seropedicae attachment assays decreased 80-fold the adhesion of the wild type to maize roots. The results suggest that N-acetyl glucosamine residues of the LPS O-antigen bind to maize root lectins, an essential step for efficient bacterial attachment and colonization.